PROGRAM KEMITRAAN MASYARAKAT (PKM): ECO-ENZYM SEBAGAI STIMULATOR ENTREPRENEURSHIP SISWA SMA MUHAMMADIYAH 4 KENDAL - Atip Nurwahyunani; Ipah Budi Minarti, Rivanna Citraning Rachmawati, Eko Retno Mulyaningrum (Adiba Aisha Amira, 2022)
To realize the project to strengthen the profile of Pancasila students which is an integral part of the Merdeka Curriculum, SMA Muhammadiyah 4 Kendal requires assistance and training in the Pancasila Student Profile Strengthening Project using a project-based learning approach that is different from project-based learning in the intracurricular program. in the classroom. This is in line with the Biology Education Study Program through the Research and Community Service Institute that will collaborate with SMA Muhammadiyah 4 Kendal in implementing the Pancasila Student project through the PKM program, namely: a) Counseling and focus group discussions on management in the school environment, b) Waste management training become ecoenzymes, c) Training on processing organic waste into ecoenzymes as a form of student entrepreneurship. This PKM activity was carried out at SMA Muhammadiyah 4 Kendal for 3 months. Since August 20 - December 20, 2022. The methods used in the implementation of this PKM activity are lectures, simulations or demonstrations, hands-on practice, and assistance on processing eco- enzymes and their derivatives to be used as products that are worth selling as one of the creative ideas in building students Entrepreneur. The results of the activity, achieved student skills in processing waste and vegetables into ecoenzymes, an increase in students' knowledge related to ecoenzymes and their derivatives, students have knowledge about entrepreneurship through ecoenzymes.